HOW IS MASCULINE IDEOLOGY REPRESENTED IN RADITYA DIKA'S STAND-UP COMEDY? Received: 23rd June 2023; Revised: 12th September 2023, 03rd October 2023; Accepted: 07th October 2023 - Faizti, Nurfadhela; Tanjung, Sumekar (PEOPLE: International Journal of Social Sciences, 2023)
This research aims to explicate how the ideology of masculinity is represented in Raditya Dika's stand-up comedy. Stand-Up Comedy Raditya Dika (SUCRD) is a collection of stand-up comedy performances created by comedian and writer Raditya Dika since 2016. Humor centered around masculinity and all things related to it consistently features in Raditya Dika's stand-up material. Using Roland Barthes' semiotic approach, this research examines masculinity within the context of SUCRD performances, with a specific focus on one episode titled Cowok Goblok featuring two monologues. This episode serves as an illustrative example of how masculine ideology is represented. The researcher limits the scope to one episode to avoid data saturation. Two key findings emerge from this study. Firstly, masculine ideology is conveyed verbally through the use of affiliative humor and self-enhancing humor. Secondly, masculine ideology is represented through narratives about decision-making, maturity, characteristics, expectations, and appearance of men. Stand-up comedy serves as a medium and space for the perpetuation of masculinity.